Analisis Motivasi, Disiplin, Dan Kepuasan Kerja Terhadap Kinerja Karyawan Outsourcing (Studi Pada PT Bank Pembangunan Daerah Jawa Timur Tbk. Cabang Nganjuk) - Depy Tri Budi Siswanto; Imam Baehaki (Otonomi, 2021)
Employee is a central factor for a company or organization. There are various types of recruitment to choose the qualified employee for a company, the most-commonly-known in Indonesia is outsourcing. PT Bank Pembangunan Daerah Jawa Timur Tbk. uses outsourcing method to recruit some employees. There are three partners that provide 62 outsourcing employees for PT Bank Pembangunan Daerah Jawa Timur Tbk. Nganjuk branch office. Every employee should be responsible for the duty according to the high motivation, discipline, and the satisfaction of salary, benefits, success, work environment and so on. The purpose of this research are to analyze the simultaneous effect of motivation, discipline, and job satisfaction on the performance of the outsourcing employees at PT Bank Pembangunan Daerah Jawa Timur Tbk. Nganjuk branch office, the researcher uses quantitative methods in analyzing the samples. The samples were taken by saturated or census sampling technique, where all the outsourcing employees were the samples. The data collection was carried out by a questionnaire and documentation. To analyze the data, the researcher uses SPSS application: normality test, multicollinearity test, linear regression, and hypothesis testing (simultaneous test and partial test). Based on the result of the research, the researcher concludes that: (1) motivation, discipline, and job satisfaction simultaneously have a significant effect on the employee performance (0.000 <0.05(), (2) It is proven that the motivation variable (X1) has a positive and significant effect on employee performance (Y) (0.009 <0.05), (3) It is proven that discipline variable (X2) has a positive and significant effect on employee performance (Y) (0.001 <0.5), (4) It is proven that the job satisfaction variable (X3) has a significant effect on employee performance (Y) (0.016 <0.05).